Determinants for Utilization of Antenatal Care Service's among Pregnant Women Attending Specialist Hospital Bauchi, Bauchi State - Babangida, Anas; Bashir Sulaiman; Abubakar, Saratu; Salisu, Umar Muhammad (THRIVE Health Science Journal, 2026)
This research conducted to determine the utilization of antenatal care services among pregnant women attending specialist hospital Bauchi state. Three research objectives and three research questions guided the study. Literature where review on effects of culture on ANC services, socio economic factors on utilization of ANC services and attitudes and health care services on the utilization of ANC services among pregnant women. The study adopted description research survey design and purposive sampling technique was used to select 90 patients from the study area. The instrument used for the data collection was structured questionnaire. 90 questionnaires were distributed to 90 respondents with the help of research assistance. The data collected was analyzed using frequency distribution table and percentage. Based on the research findings, it was revealed that cultural belief of different kind, low socio-economic status and attitude of healthcare providers are factors that influence the utilization of antenatal care services among pregnant women attending specialist hospital Bauchi. the findings the researcher recommended that the health care provider should help in educating the pregnant women on the need and importance of antenatal clinic attendance, culture and religious belief that can affect health negatively should be discouraged through community mobilization and participation towards factors that are harmful to health. Adequate provision of qualified health personnel to manage the health facilities and health unit should be fully equipped. finally, Government should do much within its limited resources to provide free ANC services at all level of health institutions and to all groups of pregnant women and Community religious, leaders should be involved in promoting ANC services.